Contributions to yield, nitrogen fixation and transfer by local and exotic legumes in tropical grass-legume mixtures in Western Samoa - Reynolds, SG (1982)
Exotic legumes (Calopogonium mucunoides, Centrosema pubescens, Pueraria phaseoloides, Macroptilium atropurpureum) and indigenous legumes (Desmodium heterophyllum, Mimosa pudica, Vigna luteola) were compared for dry matter (DM) and crude protein (CP) production, nitrogen fixation and nitrogen transfer when grown separately with Panicum maximum (tall guinea grass) and Brachiaria miliiformis (Cori grass). Results were compared with those for grass alone receiving five levels of N (0, 56, 112, 224 and 448 kg N ha-1 year. Mean DM production was significantly higher with exotic legume–grass mixtures. Crude protein and amount of N fixed were also higher with exotic legume–grass mixtures but differences were not significant. Apparent N fixation for the six legumes ranged from 31 to 136 kg ha-1 year-1 with tall guinea and from 83 to 182 kg ha-1 year-1 with cori grass with the puero-calopo-grass mixing fixing > 130 kg ha-1 year-1 in both trials. Apparent N transfer from legume to associated grass ranged from 5 to 23 kg ha-1 year-1 with tall guinea and from 13 to 42 kg ha-1 year-1 with cori grass. Although exotic legumes fixed more N, significantly higher percentages were transferred by local legumes.